The impact of full-fat Hermetia illucens larvae meal on the health and immune system function of broiler chickens - Tykałowski Bartłomiej; Koncicki Andrzej; Kowalczyk Joanna; Śmiałek Marcin; Bakuła Tadeusz; Murawska Daria; Sobotka Wiesław; Stenzel Tomasz (Journal of Veterinary Research, 2023)
Alternative protein sources have recently been attracting growing interest as potential components of livestock nutrition. This study evaluated the effect on broiler health of replacing the soybean protein component of poultry feed with processed insect protein from farmed Hermetia illucens (HI) larvae.